Keragaman Rhizomikrobiom Bawang Merah dan Penekanan Penyakit Moler dengan Perlakuan Bacillus spp. dan Trichoderma asperellum - Sundari, Dini; Wibowo, Arif; Joko, Tri; Widiastuti, Ani; Pustika, Arlyna Budi (Jurnal Fitopatologi Indonesia, 2023)
Twisted disease (Fusarium spp.) is an endemic disease that reduces shallot production in the coastal land area of Samas, Bantul, Yogyakarta. The application of Bacillus spp. can suppress the twisted disease by secreting secondary metabolites and enhancing soil suppressiveness. This study aimed to determine the effectiveness of adding spraying Bacillus spp. on the disease incidence, production of shallots, and their effect on the diversity of rhizomicrobiome by culture microbe approaches. Bacillus spp. with a density 108 cfu mL-1, Trichoderma asperellum 106 cfu mL-1 was applied by spraying to the shallot. Fungicide chlorothalonil, propiconazole, and prochloraz were used to control the disease. The diversity of rhizobacteria and fungi was analyzed using the ribosomal intergenic spacer analysis (RISA) method. Based on the analysis result, the addition of spraying B. velezensis B-27, combination B. velezensis B-27 and B. cereus RC76, and T. asperellum was unable to enhance the suppression of twisted disease, but it was able to enhance the production of shallot bulbs reaching 7.10, 7.80, and 8.43 ton ha-1. Furthermore, the result revealed the diversity of the rhizomicrobiome, spraying Bacillus sp. showed 39% differences in bacterial diversity with control while T. asperellum caused 43% difference in the diversity. Spraying Bacillus spp. has not been able to suppress the incidence of twisted diseases compared to control. However, the similar disease incidence on a spraying Bacillus spp. and control showed a higher production until 70% compared to control. This result showed that the addition of spraying Bacillus spp. able to increase the tolerance of shallot plants toward twisted disease.